Constitutional Innovations in the Mechanisms of Implementation and Limitation of Human Rights and Freedoms (Systemic and Formal Legal Interpretation) - Vagharshyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The legal provisions of the Republic of Armenia Constitution with amendments from 2015, which are innovations in regard to the mechanisms of implementation and limitation of human rights and freedoms, are discussed in the Article. In this context, the constitutional concepts “organizational mechanisms and procedures necessary for the effective exercise of rights and freedoms”, “inviolability of the essence of the provisions on fundamental rights and freedoms”, “proportionality of the limitation” and “certainty of the limitation” are interpreted in the systemic and formal legal sense. These innovations in the institutes of the fundamental rights and freedoms are foreseen as important constitutional-legal guarantees for the protection of the basic rights.
Keywords: Constitution, implementation of rights, mechanism, direct action, limitations of rights, certainty, proportionality, suitable, necessary, inviolability of the essence